Investing in water for food, ecosystems, and livelihoods: an overview of the comprehensive assessment of water management in agriculture - Fraiture, Charlotte de; David, S.; Wichelns, Dennis (Elsevier, 2010)
The authors of the recently completed Comprehensive Assessment of Water Management in Agriculture (CA) concluded that there are sufficient water resources to produce food for a growing population but that trends in consumption, production and environmental patterns, if continued, will lead to water crises in many parts of the world. Only if we act to improve water use will we meet the acute fresh water challenge. Recent spikes in food prices, partially caused by the increasing demand for agricultural products in non-food uses, underline the urgent need to invest in agricultural production, of which water management is a crucial part. The world experienced similar pressure on per capita food supplies and food prices in the 1960s and 1970s, but the challenges now are different than those we experienced 50 years ago. The world's population is substantially larger, there are many more people living in poverty, and the costs of many agricultural inputs are much higher. The current situation and the long-term outlook require a fresh look at approaches that combine different elements such as the importance of access to water for the poor, providing multiple ecosystem services, rainwater management, adapting irrigation to new needs, enhancing water productivity, and promoting the use of low-quality water in agriculture. This special issue highlights the analysis behind a number of policy options identified by the CA, a five-year multi-disciplinary research program involving 700 scientists. This introductory article sets the background and context of this special issue, introduces the key recommendations from the CA and summarizes the papers in this issue.